Risks of solid cancers in patients with rheumatoid arthritis and after treatment with tumour necrosis factor antagonists. Issue 10 (13th April 2005) - Askling, J; Fored, C M; Brandt, L; Baecklund, E; Bertilsson, L; Feltelius, N; Cöster, L; Geborek, P; Jacobsson, L T; Lindblad, S; Lysholm, J; Rantapää-Dahlqvist, S; et al.
Abstract : Background: Existing studies of solid cancers in rheumatoid arthritis (RA) reflect cancer morbidity up until the early 1990s in prevalent cohorts admitted to hospital during the 1980s. Objective: To depict the cancer pattern of contemporary patients with RA, from updated risk data from prevalent and incident RA populations. To understand the risk of solid cancer after tumour necrosis factor (TNF) treatment by obtaining cancer data from cohorts treated in routine care rather than trials. Methods: A population based study of three RA cohorts (one prevalent, admitted to hospital 1990–2003 (n = 53 067), one incident, diagnosed 1995–2003 (n = 3703), and one treated with TNF antagonists 1999–2003 (n = 4160)), which were linked with Swedish nationwide cancer and census registers and followed up for cancer occurrence through 2003. Results: With 3379 observed cancers, the prevalent RA cohort was at marginally increased overall risk of solid cancer, with 20–50% increased risks for smoke related cancers and +70% increased risk for non-melanoma skin cancer, but decreased risk for breast (−20%) and colorectal cancer (−25%). With 138 cancers, the incident RA cohort displayed a similar cancer pattern apart from non-decreased risks for colorectal cancer. TNF antagonist treated patients displayed solid cancer (n = 67) risks largely similar to those of other patients with RA. Conclusion: The cancer pattern in patients treated with TNF antagonists mirrors those of other contemporary as well as historic RA cohorts. The consistent increase in smoking associated cancers in patients with RA emphasises the potential for smoking cessation as a cancer preventive measure in RA.